2019
DOI: 10.21614/chirurgia.114.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Diaphragmatic Lesions - Considerations Over a Series of 15 Consecutive Cases

Abstract: Introducere: Leziunile diafragmatice sunt produse prin traumatisme toraco-abdominale închise sau deschise. Acestea sunt leziuni potenţial letale prin hernierea organelor abdominale în cavităţile pleurale şi prin severitatea leziunilor asociate. Scopul acestui studiu a fost analizarea manifestărilor clinice şi a managementului pacienţilor internaţi în clinica noastră cu diagnosticul de ruptura traumatică a diafragmului. Material şi metodă: Am efectuat un studiu retrospectiv pe o perioadă de 5 ani, în care am in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
3
0
5
Order By: Relevance
“…Of the 8 diaphragmatic injuries caused by blunt mechanism, investigators found these to have larger tears with an abdominal viscera herniation rate of 75%. Their mortality rate was 20% and deaths were attributed to the associated severe traumatic injuries [9].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 8 diaphragmatic injuries caused by blunt mechanism, investigators found these to have larger tears with an abdominal viscera herniation rate of 75%. Their mortality rate was 20% and deaths were attributed to the associated severe traumatic injuries [9].…”
Section: Discussionmentioning
confidence: 99%
“…De los pacientes con trauma contuso, principalmente víctimas de accidentes automovilísticos o caídas de altura, 0.7-8% presenta lesiones diafragmáticas; mientras que hasta 15% se observan en los pacientes con lesiones penetrantes. 1,2 De 65-75% de las lesiones ocurren del lado izquierdo, 1,2 Figura 1: Radiografía de tórax con elevación del hemidiafragma derecho.…”
Section: Discussionunclassified
“…2 Únicamente 13% de las lesiones son del lado derecho, con una proporción de 25:1 y 2% cursa con lesión bilateral. 1,3 La fisiopatología de una ruptura diafragmática traumática proviene de una elevación súbita de presión intraabdominal por compresión de alta energía o secundaria a trauma abdominal, lo que puede conducir a la ruptura localizada en la parte posterior del diafragma. 4 Otro mecanismo que puede causar la ruptura se da cuando el impacto es lateral y hay fracturas costales en las cuales se rompen las fijaciones periféricas del diafragma.…”
Section: Discussionunclassified
See 2 more Smart Citations